Transport logistics - McKinnon, Alan C. 1953-; Button, Kenneth 1948-; Nijkamp, Peter (Elgar reference collection, 2002)
The volume is divided into 13 sections covering the full spectrum of research in the field, including the modelling of freight flows, just-in-time delivery, modal split, vehicle routing and utilisation, the environmental impact of freight transport operations, city logistics and telematics and the deregulation of freight markets